2016
DOI: 10.1117/12.2218649
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of OCT images with vinyl polysiloxane (VPS)

Abstract: Several studies have shown that optical coherence tomography (OCT) can be used to measure the remaining enamel thickness and detect the location of subsurface lesions hidden under the sound enamel. Moreover studies have shown that high refractive index liquids can be used to improve the visibility of subsurface lesions in OCT images. In this study, we demonstrate that vinyl polysiloxane (VPS) impression materials which are routinely used in dentistry can be used to enhance the detection of dentinal lesions on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Previous studies by Kang et al. reported that the application of transparent vinyl polysiloxane (VPS) to the teeth could significantly improve the OCT imaging depth and signal intensity, [ 28 , 29 ] which had good biocompatibility. [ 30 ] Thus, it has a great potential in maintaining skull transparency chronically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies by Kang et al. reported that the application of transparent vinyl polysiloxane (VPS) to the teeth could significantly improve the OCT imaging depth and signal intensity, [ 28 , 29 ] which had good biocompatibility. [ 30 ] Thus, it has a great potential in maintaining skull transparency chronically.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we solidify the skull clearing maintenance reagent by combining the periodic and continuous irradiation, during which the temperature rise is less than 1 °C (Figure S9, Supporting Information), whereas continuous irradiation normally induces over 19 °C rise maximumly (Figure S10, Supporting Information). Previous studies by Kang et al reported that the application of transparent vinyl polysiloxane (VPS) to the teeth could significantly improve the OCT imaging depth and signal intensity, [28,29] which had good biocompatibility. [30] Thus, it has a great potential in maintaining skull transparency chronically.…”
Section: Discussionmentioning
confidence: 99%